2012
DOI: 10.1309/ajcp9q6ovlvshtmy
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of TIM-3 in Lung Cancers

Abstract: T-cell immunoglobulin- and mucin domain-3-containing molecule 3 (TIM-3) is a membrane protein expressed in various kinds of immune cells and plays a pivotal role in immune regulation. Recently, TIM-3 was reported to be expressed aberrantly in melanoma cells, contributing to the low adhesion ability of tumor cells and promoting the survival of melanoma cells. We investigated TIM-3 expression in non-small cell lung cancers (NSCLCs), and further analyzed whether the aberrant expression of TIM-3 is related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 29 publications
5
42
0
Order By: Relevance
“…[27][28][29] While PD-1 was only expressed on tumor cells in 10% of the unpretreated samples, TIM-3 expression was observed on tumor cells in both unpretreated and pretreated samples. More unpretreated samples had TIM-3 C TILs compare with the pretreated, taken into consideration that our number of pretreated samples is rather low.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] While PD-1 was only expressed on tumor cells in 10% of the unpretreated samples, TIM-3 expression was observed on tumor cells in both unpretreated and pretreated samples. More unpretreated samples had TIM-3 C TILs compare with the pretreated, taken into consideration that our number of pretreated samples is rather low.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TIM-3 in CD4+ T cells was associated with nodal metastasis and advanced cancer stage [61]. As well as being present in T cells, TIM3 has been reported in NSCLC in 86.7% of NSCLC tumor cells and is associated with T stage and histology and is an independent prognostic factor in NSCLC (relative risk of 4.481; 95% CI, 1.790–11.22) [62]. In preclinical models, the combined inhibition of TIM3 and PD-1 has been reported to be more effective than inhibiting either pathway alone in a range of solid tumors [59,63,64].…”
Section: Co-inhibitory Interactionsmentioning
confidence: 99%
“…T cell immunoglobulin mucin-3 (TIM-3), a membrane protein, plays a pivotal role in immune regulation [7]. Current studies have demonstrated a strong correlation between TIM-3 expression and tumor-associated immune suppression.…”
mentioning
confidence: 99%